2022
DOI: 10.3390/d14070562
|View full text |Cite
|
Sign up to set email alerts
|

Parasites, Bacteria and Viruses of the Edible Dormouse Glis glis (Rodentia: Gliridae) in the Western Palaearctic

Abstract: An overview of the parasites, bacteria and viruses of Glis glis (Rodentia, Gliridae) inhabiting the Western Palearctic is given. A total of 85 articles published from 1895 to 2021 were reviewed and analysed in our study. According to the literature’s data, 104 species associated with G. glis are recorded: 4 viruses, 8 Protozoa, 6 Cestoda, 6 Trematoda, 4 Nematoda, 1 Heteroptera, 2 Anoplura, 39 Siphonaptera and 34 Acari. The most studied group is ectoparasites. To a lesser extent, parasitic worms in G. glis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Furthermore, it became possible to clarify species affiliation of this genus's cestodes found by other authors in various regions of the Palearctic. Studies by most authors either represent faunistic summaries on helminths of shrews from different parts of the Palearctic without inclusion of any morphological traits of the found cestodes or contain data that do not match diagnoses of modern species; this state of affairs casts doubt on the correctness of their identification (Arzamasov et al 1969;Anikanova et al 2001Anikanova et al , 2002Irzhavsky & Gulyaev 2002;Haukisalmi 2015;Kirillov et al 2018;Nikonorova et al 2019). Publications containing not only information about finds of Neoskrjabinolepis species in various hosts but also morphometric features (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it became possible to clarify species affiliation of this genus's cestodes found by other authors in various regions of the Palearctic. Studies by most authors either represent faunistic summaries on helminths of shrews from different parts of the Palearctic without inclusion of any morphological traits of the found cestodes or contain data that do not match diagnoses of modern species; this state of affairs casts doubt on the correctness of their identification (Arzamasov et al 1969;Anikanova et al 2001Anikanova et al , 2002Irzhavsky & Gulyaev 2002;Haukisalmi 2015;Kirillov et al 2018;Nikonorova et al 2019). Publications containing not only information about finds of Neoskrjabinolepis species in various hosts but also morphometric features (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cestodes of the genus Neoskrjabinolepis Spassky, 1947 are characterized by high species richness and widespread occurrence in the Holarctic, as evidenced by their finds in various species of shrews Sorex (Mammalia: Soricidae) during faunal studies in various regions of Eurasia (from the Pyrenees to Chukotka and the Japanese islands) and North America (Alaska) (Zarnowski 1955;Prokopič 1958;Schaldybin 1964;Arzamasov et al 1969;Vaucher 1971;Prokopič & Matsaberidze 1972;Roots 1992;Novikov 1995;Hanzelová & Ryšavý 1996;Tkach & Zhumabekova 1996;Sawada 1999;Anikanova et al 2001Anikanova et al , 2002Irzhavsky & Gulyaev 2002;Binkiene 2006;Haukisalmi 2015;Kirillov et al 2018;Kornienko et al 2022c).…”
Section: Introductionmentioning
confidence: 99%
“…Of those, N. autumnalis has been known as widely distributed within the geographic range of G. glis ; however, its status should be verified as likely to represent several taxa. The occurrence of N. vernalis on G. glis reported by Kirillov et al ( 2022 , referring to Kepka 1964 ) should be confirmed due to the inconsistency of data provided in the original publication.…”
Section: Introductionmentioning
confidence: 86%
“…To date, 14 chigger species, identified based on morphology, have been recorded from this host. The inventory of records, provided by Kirillov et al ( 2022 ), comprising 12 species— Ascoschoengastia latyshevi (Schluger), Hirsutiella zachvatkini (Schluger), Leptotrombidium europaeum (Daniel et Brelih), Leptotrombidium silvaticum Hushcha et Schluger, Miyatrombicula muris (Oudemans), Neotrombicula austriaca Kepka, Neotrombicula inopinata (Oudemans), Neotrombicula japonica (Tanaka, Kaiwa, Teramura et Kagaya), Neotrombicula nagayoi (Sasa, Hayashi, Sato, Miura et Asahina), Neotrombicula vernalis (Willmann), Neotrombicula vulgaris (Schluger), and Schoutedenichia sp.—should be completed with two more species, recorded by Kepka ( 1964 ) and Mulyarskaya ( 1965 ): Neotrombicula autumnalis Shaw and Neotrombicula talmiensis (Schluger). Of those, N. autumnalis has been known as widely distributed within the geographic range of G. glis ; however, its status should be verified as likely to represent several taxa.…”
Section: Introductionmentioning
confidence: 99%
“…species from orders such as Coleoptera, Diptera, Siphonaptera, Hemiptera, Hymenoptera, and Lepidoptera), and even invertebrates that are not typically associated with nest boxes on trees such as Isopoda, Gastropoda, and Myriapoda [9][10][11][12][13][14][15][16]. Much scholarly attention was paid to the presence of ectoparasites in such places related to their hosts (fleas, ticks, Diptera: Protocalliphoridae, and some mites) [17][18][19][20][21][22][23][24]. Among the groups that are frequently observed in nest boxes, the most interesting phenomena is the presence of typical nidicoles, for whom nests are the proper type of habitat [25,26].…”
Section: Introductionmentioning
confidence: 99%